Potential of Traditional Medicinal Plants and Utilization in Galela Community, North Halmahera: Case Study in Soatobaru Village, Galela Barat Sub District - Kastanja, Ariance Yeane; Patty, Zeth (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
This research was carried out in Soatobaru Village, West Galela sub District for 2 months, aims to identify the types of plants used by the Galela community as traditional medicinal ingredients, including sections and methods of processing. The method used is the survey method where the team conducts direct observations to the field and then takes the potential drug specimen, as well as conducting interviews with respondents for information on plant parts and processing methods. Data analysis is carried out descriptively based on the results of research and presented in the form of graphics, images and tables. The results showed that 27 species were found and came from 24 medicinal plants at the study site, which could be grouped in 6 habitus, namely trees, shrubs, palma bushes, vines and herbs. There are 15 types that use leaves, 12 types of use fruit, 3 types used seeds, 2 types using roots and tubers, and 1 type using fruit water.